Gaze Behavior of Children with ASD toward Pictures of Facial Expressions - Matsuda, Soichiro (Autism Res Treat, 2015)
Atypical gaze behavior in response to a face has been well documented in individuals with autism spectrum disorders (ASDs). Children with ASD appear to differ from typically developing (TD) children in gaze behavior for spoken and dynamic face stimuli but not for nonspeaking, static face stimuli. Furthermore, children with ASD and TD children show a difference in their gaze behavior for certain expressions. However, few studies have examined the relationship between autism severity and gaze behavior toward certain facial expressions. The present study replicated and extended previous studies by examining gaze behavior towards pictures of facial expressions. We presented ASD and TD children with pictures of surprised, happy, neutral, angry, and sad facial expressions. Autism severity was assessed using the Childhood Autism Rating Scale (CARS). The results showed that there was no group difference in gaze behavior when looking at pictures of facial expressions. Conversely, the children with ASD who had more severe autistic symptomatology had a tendency to gaze at angry facial expressions for a shorter duration in comparison to other facial expressions. These findings suggest that autism severity should be considered when examining atypical responses to certain facial expressions.